Educational outcome of inquiry-based teaching learning method versus traditional learning among second phase medical students in pharmacology - Choudhury, Urmi; Pathak, Swanand; Thakuria, Kahua Das; Sarmah, Bhaswati Kashyap (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Pharmacology is a core discipline in medical education, bridging basic and clinical sciences. Traditional lecture-based teaching promotes factual recall but may not sufficiently develop analytical and problem-solving skills. Inquiry-based teaching-learning (IBTL) emphasizes critical thinking, active participation, and self-directed learning. Methods: A prospective, cross-sectional educational intervention was conducted among 92 phase-II MBBS students of Nagaon Medical College, Assam. Students were divided into group A (IBTL) and group B, traditional teaching method (TTM). Identical topics were taught in both groups. Assessment included pre- and post-tests, student feedback, and faculty perception. Data were analyzed using paired and unpaired t tests (SPSS v21). Results: IBTL produced significant improvement in post-test scores (p<0.001) and led to higher student engagement and satisfaction. Faculty feedback reflected 100% agreement that IBTL enhanced conceptual understanding and critical thinking. Although traditional teaching yielded higher factual recall for the topic “vitamins” (p=0.004), IBTL supported better long-term retention, motivation, and deeper understanding. Conclusions: IBTL is more effective than traditional methods in promoting active learning, conceptual clarity, and critical thinking. A blended model combining both approaches is recommended for optimal pharmacology education.